Glia Maturation Factor β as a Novel Independent Prognostic Biomarker and Potential Therapeutic Target of Kidney Renal Clear Cell Carcinoma - Zhu, Tong; Wang, Tianyu; Feng, Zijun; Gao, Furong; Zhang, Jieping; Jin, Caixia; Tian, Haibin; Xu, Jingying; Chen, Hao; Ou, Qingjian; Wang, Juan; Xu, Guotong; et al. (Frontiers in Oncology, 2022)
Kidney renal clear cell carcinoma (KIRC) has the highest mortality rate and potential for invasion among renal cancers. The diagnosis and treatment of KIRC are becoming challenging because of its diverse pathogenic mechanisms. Glia (GMFB) is a highly conserved growth and differentiation factor for glia cells and neurons, and it is closely associated with neurodegenerative diseases. However, its role in KIRC remains unknown. The present study integrated bioinformatics approaches with suitable meta-analyses to determine the position of GMFB in KIRC. There was a significant decrease in Gmfb expression in KIRC kidneys compared with normal controls. Gmfb expression was negatively associated with pathologic stage, T and M stages, and histologic grade. Univariate and multivariate analyses showed that elevated Gmfb expression was an independent factor for a favorable prognosis. Furthermore, the nomogram verified that Gmfb is a low-risk factor for KIRC. Knockdown of Gmfb in Caki-2 cells increased viability and decreased p21 and p27 levels. Overexpression of Gmfb inhibited Caki-2 cell proliferation, migration, and invasion and decreased mitochondrial membrane potential. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses considering Gmfb co-expressed differentially expressed genes (DEGs) showed that collecting duct acid secretion and mineral absorption ranked were the most important upregulated and downregulated DEGs, respectively. The upregulated hub genes for DEGs were mainly involved in nucleosome assembly, nucleosome organization, and chromatin assembly, and the downregulated hub genes were primarily associated with keratinization. The ratio of tumor-infiltrating immune cells in KIRC tissues was evaluated using CIBERSORTx. The results showed that the Gmfb expression was significantly positively correlated with macrophage M2 cells and mast resting cell infiltration levels and negatively correlated with T follicular helper, T regulatory, and B plasma cell infiltration levels. The former cell types were associated with a beneficial outcome, while the latter had a worse outcome in patients with KIRC. In summary, this study identified GMFB as a novel independent biomarker and therapeutic target for KIRC, and it provides a helpful and distinct individualized treatment strategy for KIRC with a combination of molecular targets and tumor microenvironment.